Optimasi Desain Ulang Stator Pompa Progressive Cavity Dengan DfD dan Solidworks CAD - Riki Candra Putra (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2022)
Progressive cavity pump designs generally have a stator component in the form of a solid hollow cylinder and a rotating rotor, because of the constraints faced by technicians specifically on the PC type pump, namely the need for lifting equipment, and some special equipment and very time consuming pump assembly. long time, due to the complicated pump design. Because these problems can make progressive cavity pumps become waste in the company due to the lack of good maintenance for this type of pump. Therefore, it is necessary to redesign and optimize the stator design in order to obtain a faster assembly time, easier pump maintenance and cheaper maintenance costs. By using the principles of Design for Disassembly (DfD), and assisted by CAD software and flow simulation analysis so that it can make it easier for researchers to redesign and optimize products. After redesigning the stator into a split stator and a simpler rotor design, the flow simulation analysis found that the flow rate and pressure of the DfD pump did not experience very large changes and did not affect the overall pump performance. The number of tools needed to assemble the stator and rotor of the pump after DfD is 7.14% cheaper than the pump before DfD. The processing time of the DfD pump stator assembly stages is 23% faster and the DfD pump rotor assembly is 14.3% faster than the pump before DfD. The percentage of the difference in the price of components that are wasted (waste) in DfD pumps is 10.5% less than non-DfD pumps when replacing the stator and rotor.